Meta-analysis of Arabidopsis thaliana microarray data in relation to heat stress response - Chaddad, Zohra; Kaddouri, Kaoutar; Smouni, Abdelaziz; Missbah El Idrissi, Mustapha; Taha, Kaoutar; Hayah, Ichrak; Badaoui, Bouabid (Frontiers in Plant Science, 2023)
Increasing global warming has made heat stress a serious threat to crop productivity and global food security in recent years. One of the most promising solutions to address this issue is developing heat-stress-tolerant plants. Hence, a thorough understanding of heat stress response mechanisms, particularly molecular ones, is crucial. Although numerous studies have used microarray expression profiling technology to explore this area, these experiments often face limitations, leading to inconsistent results. A random effects meta-analysis can help overcome these limitations by employing advanced statistical methods. For this reason, a meta-analysis of 16 microarray datasets related to heat stress response in A. thaliana was conducted. The analysis revealed 1,972 significant differential expression genes between control and heat-stressed plants (826 over-expressed and 1,146 down-expressed) including 128 differentially expressed transcription factors from different families. The most significantly enriched biological processes, molecular functions, and KEGG pathways for over-expressed genes included heat response, mRNA splicing via spliceosome, spliceosome pathways, unfolded protein binding, and heat shock protein binding. In contrast, the most significantly enriched categories for down-expressed genes included cell wall organization or biogenesis, protein phosphorylation, transmembrane transporter activity, ion transmembrane transporter, biosynthesis of secondary metabolites, and metabolic pathways.